DAMPAK PERSEPSI HARGA DAN MERCHANDISE TERHADAP KEPUASAN SERTA PEMBELIAN ULANG - ERWIN SYAHPUTRA; APRILIA DIAN EVASARI (STIE Indonesia Malang, 2022)
Retail trade or now often called retail trade, even shortened to retail business, is a business activity of selling goods or services to individuals for their own, family, or household needs. In this study, customer satisfaction is influenced by two variables, namely the perception of price and merchandise and the impact of this satisfaction is the intention to repurchase at the Golden Swalayan retail Kediri. The results of this study indicate that prices and merchandise have a significant effect on customer satisfaction and customer satisfaction has a significant effect on repurchase intentions. The results of this study also indicate that the merchandising variable has a dominant influence on customer satisfaction.Keywords: price perception, merchandise, satisfaction, repurchase